The localisation and stability of the CENP-F protein are regulated by importin beta and microtubules in mitotic cells - Ludovica Altieri; Michela Damizia; Paola Rovella; Vincenzo Costanzo; Morena Mancini; Patrizio Di Micco; Matteo Marzi; Daniela Trisciuoglio; Veronica Morea; Patrizia Lavia (Scientific Reports)
Abstract CENP-F is a large protein acting in fundamental cell cycle processes, including nuclear envelope breakdown, mitotic microtubule function and chromosome segregation. These activities are mediated by specific CENP-F protein elements that interact with microtubules, motor proteins, centrosomes and kinetochores. CENP-F is then ubiquitinated and degraded in late mitosis. The C-terminal region of CENP-F contains regulatory elements, including a region required for nuclear localisation in interphase and a KEN box driving proteolysis in late mitosis. Here we show that CENP-F generates proximity ligation products with importin beta during mitosis. Furthermore, induction of importin beta overexpression influences CENP-F at two levels: it alters CENP-F mitotic localisation, promoting its accumulation at spindle poles and decreasing its association with kinetochores, and also causes its persistence in the late mitotic window in which CENP-F normally disappears, in a process that requires microtubule integrity and dynamics. These data implicate therefore importin beta in spatial and temporal control of CENP-F during mitosis, and uncover a functional interplay between CENP-F’s ability to regulate mitotic microtubules and, in turn, a protective role of microtubules against CENP-F premature ubiquitination.